Attitudes of rural men towards the advancement of rural women : a study of Thandanani and Umngazi maize producing projects - Neno, Thembisile Wiseman (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MPhil (Sociology and Social Anthropology))--University of Stellenbosch, 2007.